Gregory, the terrible eater - Sharmat, Mitchell (Four Winds Press : Macmillan, 1985)
A very picky eater, Gregory the goat refuses the usual goat diet staples of shoes and tin cans in favor of fruits, vegetables, eggs, and orange juice.